Single-cell RNA sequencing depicts metabolic changes in children with aplastic anemia - Zhou, Qin; Huang, Lifen; Liu, Yong; Huang, Junbin; Wen, Luping; Yang, Jing; Liang, Jintang; Chen, Yun; Chen, Chun (Frontiers in Oncology, 2023)
Introduction Aplastic anemia (AA) is a bone marrow hematopoietic failure syndrome mediated by immune cells. The mechanism of this immune disorder is not well understood and therapeutic strategies still need to be improved. Methods Studies have found that abnormalities in metabolisms promote the survival of AA cells. In recent years, an increasing number of studies have reported the immunosuppressive therapy for the treatment of AA. In this study, we analyzed the transcriptome of AA from peripheral blood compared with healthy donors by single-cell sequencing and identified the affected metabolic pathways including lysine degradation. We demonstrated that the metabolic abnormalities of T lymphocytes mainly focus on glycolysis/gluconeogenesis. In addition, the metabolic abnormalities of natural killer cells concentrated in oxidative phosphorylation. Results The key genes involved in abnormal metabolic processes were Neustein neurotrophic factor (NENF), inositol polyphosphate-4-phosphatase type II B (INPP4B), aldo-keto reductase family 1, member C3 (AKR1C3), and carbohydrate (N-acetylglucosamine-6-O) sulfotransferase 2 (CHST2) by differential gene expression analysis. Discussion Molecule interaction analysis showed that tumor necrosis factor superfamily, member 12 (TNFSM12) in tumor necrosis factor (TNF) signaling was broadly activated in AA. In conclusion, we suppose that the treatment of the immune cells’ abnormal metabolic pathway may contribute to the development of novel strategies to treat AA.